Symposium 6: Collaborative Learning: Research Simulator - Dhariwal, Kewal S. (Proceedings of the International Conference on Networked Learning, 2006)
What: This paper reports on the results of participative action research by multiple teams of participants who played various roles and fostered the evolution of an integrated research and business simulation environment by sharing data, making decisions visible and discussing solutions in both a competitive and a collaborative environment. Why: Collaborative Networked Learning is needed for the training of effective management and operation of global corporate entities and in understanding the value of integrating information systems between organizations that collaborate and compete with each other in different times and markets. This is necessary since competition, in business today, is between supply chains of competing collectives of organizations, each seeking a larger market share and bigger profits and where changes in partnerships come at an ever increasing pace. Who: Managers, students, tutors & administrators of classroom, online courses, and boardroom based professional development programs. When: During the period July 2003-December 2005 using the simulator located at www.sccori.com Where: In online courses, residential programs, in bricks and mortar classrooms and in the boardrooms of major corporations. How: Using an internet browser-based online business simulator and internet communications tools allowing participants to play the roles of Retailer, Wholesaler, Distributor and Manufacturer in a number of business simulations with variable parameters. Participants experience simulations and learn by doing, build problem solving skills, develop strategies, plan, negotiate, share, build trust and implement solutions. Results: The networked management learning business simulator improves the systems dynamics models from MIT and the Systems Dynamics Society by at least two orders of magnitude. Results indicate that participants move from an individualistic competitive stance to a collaborative team-based solutions focus to threats and problems faced by their supply chain during increasingly challenging business simulations.